ANALISIS IMPLIKASI PERATURAN BI NO. 13/20/PBI/2011 TERHADAP PENERIMAAN DEVISA HASIL EKSPOR DI BANK X - , Awullia Husein, Dr. Sony Warsono, MAFIS., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bank Indonesia has issued a regulation PBI No.13/20/PBI/2011 concerning the duty of exporters to receive export proceeds (DHE) into the country through a foreign exchange bank. This is a one way whereby the government controls export proceeds as another source funding for foreign exchange supplies in the domestic market, apart from portfolio investments from foreign direct investment. The regulation has broad implications, not only to the stability of the national economy, but also to the exporters and foreign exchange banks. This study wants to analyze the impact and implications of the central bank regulation in Bank X, as well as predicting the receipt of export proceeds in Bank X for years to come. Therefore, this study aimed to: (i) analyze the impact before and after BI regulation on export proceeds commenced, (ii) predict the receipt of export proceeds of Bank X in the next two years. The research methodology used was a qualitative and quantitative analysis. One of them is to test the difference between the Means of export proceeds period before and after the BI regulation by statistics. After that, export proceeds will be forecasted using least square method with double-log model. The results of this study showed that Bank X has been able to significantly increase the number of export proceeds received after the commenced of BI regulation, furthermore it has a positive effect on earnings of Bank X as one of the major foreign exchange bank in Indonesia. Also it is predicted that in December 2014, Bank X will received the export proceeds amounting USD 1.03 billion. Therefore, it is advisable for Bank X management to maximize revenue, of which the most important are: (i) provide additional services such as online reporting for clients export activities, and (ii) provide an adequate number of human resources with additional one permanent staff who has an export and import knowledge, good communication analytical skills to assist clients in dealing with ever-increasing export proceeds transactions.